Միքայել Սեբաստացի (Բրգնիկցի) նոր նահատակը - Սարգսյան, Նոննա («Նաիրի» հրատ.)
В статье исследуется житие-марторолог армянского новомученика XVIII в. Микаэла (Бргникци) Себастаци. Хотя его имя было знакомо исследователям, оно не значится в книге Г. Ачаряна и Я. Манандяна Армянские новомученики (1155-1843) и осталось неизвестным широкому кругу читателей. Сопоставив извлеченные из рукописей противоречивые биографические данные, мы полагаем, что Микаэл родился в 1651 г., был посвящен в сан священника в 1697 г. и принял мученическую смерть 5-го мая 1708 г. Его казнь была следствием борьбы между католическими и апостольскими (эчмиадзинскими) армянами в эпоху правления османских правителей. Впервые публикуются три стихотворения: житие-мартиролог, похвальная ода и эпитафия. Текст первого составлен на базе трех рукописей. Устанавливается также, что другой инок по имени Микаэл Себастаци, монах Бзоммарского монастыря, скопировавший несколько рукописей, был внуком новомученика. Житие-мартиролог Микаэла (Бргникци) Себастаци представлен в историческом, политическом и конфессиональном контексте своей эпохи. This article examines the life and martyrdom of Michael (Brgniktsi) Sebastatsi (18th century). Although his name was known to scholars, his martyrdom was not included in H. Acharyan‟s and H. Manandyan‟s Armenian New Martyrs (1155-1843). So he remained unknown to the wide readership. Relying on rather contradictory biographical information found in manuscripts, thе present study clarifies some details of Michael Sebastatsi‟s biography and verifies some dates about his life and work. It is assumed that Michael was born in 1651, was ordained priest in 1697 and martyred on May 5, 1708. His martyrdom was the result of conflicts between Catholic and Apostolic Armenians, intentionally instigated by the interventions of Turkish rulers. The article also contains three poems, published for the first time: Michael‟s martyrology, his panegyric and epitaph. The text of the first poem is based on a collation of three manuscripts. It is also mentioned that another priest named Michael, a monk of the Bzommar monastery, was his grandson and the scribe of a number of manuscripts. In the course of this study, the life of the new martyr Michael Sebastatsi is presented within the historical, political and religious context of the time.
Keywords: Ձեռագրեր; Սրբերի վարք